The princess bride [videorecording (Blu-Ray)] - Elwes, Cary, 1962-; Patinkin, Mandy; Sarandon, Chris; Guest, Christopher; Andre, the Giant, 1946-1993; Wright, Robin, 1966-; Shawn, Wallace (MGM Studios : Twentieth Century Fox Home Entertainment, 2017)
When the beautiful maiden Buttercup hears that her true love Westley is dead, she reluctantly agrees to marry the loathsome Prince Humperdinck. After Westley returns to rescue Buttercup, the two begin an epic adventure filled with fencing, fighting, giants, monster, miracles, true love and hilarity!